CGIAR germplasm health units apply a systems approach to germplasm seed health protection for conservation and safe international distribution - Kumar, Lava; Alakonya, Amos; Castellion, Martina; Cuervo, Maritza; Dawit, Woubit; Kreuze, Jan; Kumari, Safaa; Massart, S.; Beatriz Muller Cadenillas, Giovanna; Onaga, Geoffrey (The International Society for Plant Pathology, 2023)
Germplasm seed exchange from CGIAR genebanks and breeding is important to global agricultural research and development programs. Seed as a pathway for pest spread is an inherent risk for international seed exchanges. Phytosanitary controls have been established in accordance with the International Plant Protection Convention (IPPC) to protect global plant health from transboundary pest invasion. This presentation summarizes pest risks to international germplasm distribution; CGIAR Germplasm Health Units (GHUs) procedures to ensure the production and distribution of pest-free germplasm; bottlenecks to germplasm distribution, including the inadequacy of phytosanitary regulations guided by the International Standards for Phytosanitary Measures (ISPMs) of IPPC; and consequences of delayed germplasm access on crop improvement programs. It also presents the ‘CGIAR Greenpass Phytosanitary Protocol (CGPP)’ concept as a comprehensive phytosanitary compliance assurance procedure. Based on a systems approach of pest risk identification and pest risk mitigation in the germplasm seed production pipeline and the rigorous implementation of phytosanitary controls in collaboration with national plant protection organizations, the CGPP is expected to fast-track pest-free germplasm distribution to the global community.